2020
DOI: 10.1177/1076029620944471
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Biomarkers of Coagulation, Fibrinolytic, and Endothelial Functions for Evaluating the Predisposition to Venous Thromboembolism in Patients With Hereditary Thrombophilia

Abstract: The changes in the coagulation, fibrinolytic, and endothelial functions are correlated with the pathophysiology of the thromboembolic diseases during acute illness. However, these changes in patients with hereditary thrombophilia who were not in the acute stage of venous thromboembolism (VTE) are unclear. A panel of 4 biomarkers, including thrombin–antithrombin complex (TAT), plasmin-α2-plasmin inhibitor complex (PIC), tissue-type plasminogen activator/plasminogen activator inhibitor-1 complex (t-PAIC), and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…These results were in full agreement with the results reported by Zhou et al [17] ROC curve analysis showed that the AUC values of the thrombosis-related biomarkers were lower than the AUC values of the d-dimer and FDP, but their diagnostic speci city was higher. D-dimer and FDP were removed because of multicollinearity in the multivariate analysis.…”
Section: Comparison Of Diagnostic E Cacy Between the New Risk Predict...supporting
confidence: 92%
See 1 more Smart Citation
“…These results were in full agreement with the results reported by Zhou et al [17] ROC curve analysis showed that the AUC values of the thrombosis-related biomarkers were lower than the AUC values of the d-dimer and FDP, but their diagnostic speci city was higher. D-dimer and FDP were removed because of multicollinearity in the multivariate analysis.…”
Section: Comparison Of Diagnostic E Cacy Between the New Risk Predict...supporting
confidence: 92%
“…Secondly, the secretion of t-PAIC is time-dependent. [17] However, collection of blood specimens was based on the clinical need and may have affected the diagnostic e cacy. Finally, we did not further investigate the anticoagulation regimen in lung cancer patients with concomitant thrombosis.…”
Section: Comparison Of Diagnostic E Cacy Between the New Risk Predict...mentioning
confidence: 99%